Size effects in nanoparticle catalysis at nanoparticle modified electrodes: The interplay of diffusion and chemical reactions - Lin, C; Compton, R (American Chemical Society, 2017)
Electron transfer reactions mediated via nanoparticles immobilized on an electrode surface are considered in respect of catalytic processes in which solution phase species are either oxidized or reduced to form products exclusively via electron transfer with negligible reaction at the underlying supporting electrode. Specifically simulation is used to explore the effect of the nanoparticle size both for individual nanoparticles as well as ensembles of nanoparticles and a kinetic diagram developed. For a single nanoparticle its size controls the rates of diffusion of species to and from the particle so that the relative extent of the catalysis is reduced for larger particles. For an array of nanoparticles the response of the whole is sensitive not only to the particle size but also to the particle coverage since the inter-particle distance influences the extent, or otherwise, of the local overlap of the diffusion layers of neighbouring particles and hence also the extent of the catalysis. Both particle size and coverage are essential parameters to consider in evaluating possible electrocatalytic nanoparticles.